Pengelolaan Kesan Penyiar D’OZ Radio Bali dalam Program Mata Sapi - Devi Dharmayanti, Putu Ayu; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2017)
Mata Sapi is a unique radio programme that become one of D’OZ Radio Bali flagship programme. The goal of this research was to find out the process of Mata Sapi announcers impression management. This research used descriptive qualitative approach. Data were obtained by observation, interview, and documentation study. The result of this research showed that D’OZ Radio want to build a funny, exciting, relaxing, passionate and youthful impression on Mata Sapi programme. That makes Mata Sapi announcers did impression management by using jokes and unique laughing sound. Giri and Maesya should have a positive mind set and they should always be fun, humorous and professional.They have to control their emotions so there would be no hard feeling when delivering jokes. Their jokes did not feel like it was set before the show because they did it spontaneously without negotiating their jokes beforehand. The presence of another characters such as Pak Yan and Pak Tut made the announcers had to understand every characters that they played. The self disclosure of Giri and Maesya as announcers to each other develops gradually, ranging from discussion of general topics to personal discussion. These things they can convey after they familiar with each other. Keywords : Impression Management, Mata Sapi Programme, Radio Announcer, Self Disclosure